2012
DOI: 10.1521/aeap.2012.24.6.527
|View full text |Cite
|
Sign up to set email alerts
|

Developing Concurrency Messages for the Black Community in Seattle, Washington

Abstract: In the United States, Blacks are disproportionately impacted by HIV/AIDS. Sexual networks and concurrent relationships have emerged as important contributors to the heterosexual transmission of HIV. To date, Africa is the only continent where an understanding of the impact of sexual concurrency has been conveyed in HIV prevention messaging. This project was developed by researchers and members of the Seattle, WA African American and African-Born communities, using the principles of community-based participator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 49 publications
0
16
0
3
Order By: Relevance
“…While it has been argued that special interventions focusing on reducing sexual concurrency should not be pursued (Klichman and Grebler, 2010), evolving evidence suggests otherwise. As noted previously this includes findings from stochastic network models (Morris et al, 2009; Enns et al, 2011) and interventions in Uganda (Epstein, 2007) and the U.S. (Frye et al, 2013; Andrasik et al, 2012, 2015). We believe our research adds to this growing body of evidence that concurrency is a common occurrence among some Black young adults and that addressing it directly could play an important role in future efforts to reduce rates of HIV transmission in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been argued that special interventions focusing on reducing sexual concurrency should not be pursued (Klichman and Grebler, 2010), evolving evidence suggests otherwise. As noted previously this includes findings from stochastic network models (Morris et al, 2009; Enns et al, 2011) and interventions in Uganda (Epstein, 2007) and the U.S. (Frye et al, 2013; Andrasik et al, 2012, 2015). We believe our research adds to this growing body of evidence that concurrency is a common occurrence among some Black young adults and that addressing it directly could play an important role in future efforts to reduce rates of HIV transmission in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Frye et al (2013) conducted an HIV prevention intervention for African American men in New York City, where they observed a significant reduction in concurrency from baseline to three-month follow-up. Using a community-based participatory research approach, Andrasik et al (2012) developed simple messages on concurrency that they then used as the focus of an HIV prevention campaign for the Black community (both African-American and African-born) in Seattle, Washington. A preliminary evaluation of the campaign (Andrasik, Clad, Bove, Tsegaselassie, & Morris, 2015) yielded positive changes in knowledge, attitudes, and behavioral intentions regarding concurrency.…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of this process have been reported in a previous paper (20), but we summarize them here, as the feasibility and acceptability of this intervention is based on this process.…”
Section: Methodsmentioning
confidence: 98%
“…This recognition has led to the development of many innovative HIV prevention media campaigns on concurrency in sub-Saharan Africa (those developed by Population Services International may be viewed here: http://cptoolkit.hivsharespace.net/pages/4-mass-media.html). As described in a previous paper (20) it also inspired the “Community Action Board” (CAB) of the University of Washington (UW) Center for AIDS Research (CFAR) to partner with researchers and local Public Health officials to develop this project to assess the feasibility and acceptability of concurrency messaging for HIV prevention in the Black community in Seattle and King County, Washington. The project piloted a multifaceted grassroots and local media social marketing campaign.…”
Section: Introductionmentioning
confidence: 99%
“…Formative research processes for developing HIV prevention messages have been previously reported (Andrasik et al, 2012; Horner et al, 2008; Uhrig, Eroglu, Bann, Wasserman, & Guenther-Grey, 2010; Wright, Fortune, Juzang, & Bull, 2011). Most recently, Andrasik and colleagues outlined the development of a media campaign that directly targeted participation in sexual networks (Andrasik et al, 2012) and included extensive discussion of preproduction research.…”
mentioning
confidence: 99%